Multiuser cyclic shift keying spread spectrum underwater acoustic communication - Cheng-bing HE; Shao-jing JING; Fei HUA; Rui XI; Rui-yu ZHANG; Wen-tao SHI; Qun-fei ZHANG (Tongxin xuebao)
Aiming at the problem of low data rate and high receiver complexity of existing direct sequence spread spectrum code division multiple access (DS-CDMA),a novel code division multiple access (CDMA) using cyclic shift keying (CSK) signaling,namely CSK-CDMA,was proposed for multiuser underwater acoustic communication.The proposed method used the cyclic correlation characteristic of spread spectrum signals with M-ary modulation to provide a higher data rate than conventional.Passive time reversal technology was employed to suppress inter-code interference between users and the co-channel interference.The quasi-orthogonality of spread spectrum code was used to improve the processing gain.Multiuser communications are demonstrated with lake experimental recorded data under the condition of 5.27 km distance and complex multipath interference.The data rate is 39 bit/s/user for 6 users with bit error rate around 10-2～10-4.